Pakistan - North West Frontier Province : Public Financial Management and Accountability Assessment - World Bank (Washington, DC, 2012)
The North West Frontier Province (NWFP) is the third largest province of Pakistan. The province is landlocked and the land routes to the north are few and difficult, passing through hilly terrain. The province itself is largely mountainous, with only 30 percent cultivated land. Nearly 50 percent of the population lives in the mountainous and arid areas. The province shares a long border with eastern and southern Afghanistan and most of its population has the same ethnic background (Pushtoon) as parts of bordering Afghanistan. This document reports on a Performance Measurement Framework (PFM) assessment by describing the existing financial systems briefly and rating these systems against the laid down indicators of the PFM Performance Measurement Framework. The study has been conducted in line with the Public Financial Management Performance Measurement Framework, using six critical dimensions of performance for an open and orderly PFM system.